STABILITY ANALYSIS OF A SHIPBORNE LARGE APERTURE TELESCOPE TRACKING FRAME - LI YingJie; YANG LiBao; CHEN Tao; LI HongWen (Jixie qiangdu)
In order to gain insight into the stability of the tracking frame structure of shipborne large-aperture telescopes，the stability of typical ground-level telescope tracking frames was studied. According to the external load borne by the equipment in the case of ship， the external load was parameterized and entered into the finite element software. The pre-treatment software and finite element software were used to analyze the structural deformation under static wind load. Then， the natural frequency of the structure was solved， and a simple response spectrum analysis calculation was proposed instead of the tedious random response analysis to analyze the stability of the equipment under dynamic wind load and wave excitation. According to the stress and deformation values obtained from the results， it was ensured that the shipborne telescope tracking frame theoretically meets the strength requirements and design accuracy requirements under shipborne conditions. Under the static wind load， the maximum stress value of the tracking frame structure is about 14.07 MPa， which was less than the yield strength of steel 355 MPa， the maximum deformation variable was about 0.02 mm， which was less than the design accuracy error coaxiality <alternatives>ϕ <?fx-imagestate width="2.03200006" height="2.87866688"?> <?fx-imagestate width="2.03200006" height="2.87866688"?> </alternatives>0.1 mm， and the natural frequency 1~6th order mode value was 40.15 Hz， 49.65 Hz， 66.86 Hz， 82.93 Hz， 91.38 Hz， 115.89 Hz. Under dynamic wind load， the peak value of structural stress was 3.92 MPa and the maximum deformation variable was 0.01 mm， and under the excitation of ocean waves， the peak of structural stress was 5.88 MPa and the maximum deformation variable was 0.02 mm， which was less than the yield strength and design accuracy error coaxiality of steel. The error between the modal value obtained by the modal test and the calculated modal value is within 10%. Combining theoretical simulation and practical tests， the tracker structure can work normally under shipborne conditions.